401 Eliminating System xc- Signaling Between Astrocytes and Neurons Selectively Impairs Complex Cognition. (April 2022) - Simand, Gregory; Simand, Gregory J.; Hess, Evan; Kong, Linghai; Raddatz, Nicholas J.; Hurley, Matthew M; Maunze, Brian; Choi, SuJean; Geurts, Aron M.; Baker, David A.
Abstract : OBJECTIVES/GOALS: We aim to determine whether non-neuronal, non-synaptic glutamate signaling mechanisms can be targeted to produce highly specific, narrow changes in brain function that would benefit CNS disorders. To do this, we investigated cognitive changes produced through manipulating the activity of the astrocytic glutamate release mechanism system xc-. METHODS/STUDY POPULATION: System xc- (Sxc) activity was eliminated by mutating the gene Slc7a11 through pronuclear injection of zinc-finger nucleases into Sprague Dawley rat embryos to create a line of rats lacking Sxc (MSxc rats). To confirm a lack of Sxc activity, we verified that tissue from MSxc rats had a complete lack of xCT, which is the regulatory subunit of Sxc that is encoded by Slc7a11. We also verified that astrocyte cultures generated from MSxc tissue lacked cystine-evoked glutamate release. Next, we measured development (body weight), CNS regulation of metabolism, and other indicators of generalized, non-specific brain function as well as behaviors that are reliant on executive function, such as cognitive flexibility, impulse control, decision-making, and response inhibition. RESULTS/ANTICIPATED RESULTS: Eliminating Sxc was not lethal and did not impair development or produce widespread changes in brain function as is commonly observed when deleting other glutamate mechanisms. MSxc rats did not differ from wildtype in growth rate, central regulation of metabolism as reflected by absolute or diurnal changes in core body temperature, locomotor activity in a familiar or novel environment, or simple forms of cognition such as novel object recognition, or operant responding (food and cocaine-reinforced). In contrast, behaviors that rely on executive function were impaired. MSxc rats displayed deficits in cocaine reinstatement and attentional set-shifting. We anticipate MSxc rats to also show impairments in decision-making in the rat gambling task and response inhibition in the stop-signal reaction time task. DISCUSSION/SIGNIFICANCE: Eliminating Sxc activity in rats produced deficits in behaviors reliant on executive function without impacting development or simple brain function. These results highlight the potential of targeting Sxc to enhance cognition without generating therapeutically limiting adverse effects resulting from non-specific changes in brain function.